Landscape connectivity and spatial prioritization in an urbanising world: A network analysis approach for a threatened amphibian. (September 2019) - Matos, Cátia; Petrovan, Silviu O.; Wheeler, Philip M.; Ward, Alastair I.
Abstract: Habitat fragmentation affects amphibian populations worldwide. Urban expansion and associated infrastructure are a main cause of habitat degradation and loss of landscape-scale habitat connectivity. Mitigation measures such as underpasses and associated fences are implemented to reduce the impacts of development on protected species. However, such efforts focus largely on local outcomes rather than envisioning how mitigation may contribute to habitat connectivity and population persistence at the landscape scale. We used a graph-theoretic approach to model structural and functional connectivity for a widespread but declining pond-breeding amphibian, the great crested newt ( Triturus cristatus ). This involved assessing species movement among breeding ponds and associated landscapes with different levels of urban and rural development and linear barriers. We used recent regional pond survey data for great crested newts combined with published data on movement and habitat use to explore connectivity. Landscape connectivity was affected by factors such as habitat quality and quantity, scale of movement and different degrees of road permeability. Linear barriers to movement and differences in their permeability were critical for predicting their impact on both migratory and dispersal movements in Triturus cristatus . Incorporating landscape connectivity modelling which includes the impact of barriers such as roads would substantially improve population-level outcomes from mitigation schemes. An accurate understanding of the far-reaching consequences of road mitigation as well as immediate, local effects, combined with our methods of assessing road permeability could transform future mitigation efforts by directing action to places that not only improve individual survival but also maximise connectivity at the landscape-scale. Highlights: Development and linear barriers influence amphibian movements among breeding ponds during both migration and dispersal. Habitat quality, scale of movements and road permeability govern landscape-level connectivity of a pond-breeding amphibian. Network analysis under different scenarios improves the understanding of landscape dynamics. Connectivity modelling can help prioritisation in mitigation planning and long-term effectiveness of conservation schemes.